PERAN TEKS DAN KONTEKS DALAM PENAFSIRAN FILSAFAT: MENELUSURI KERAGAMAN MAZHAB PEMIKIRAN - Saumantri, Theguh; Saefuddin, Didin (UIN Sumatera Utara Medan, 2025)
The interpretation of philosophical texts is always closely tied to social, historical, cultural, and biographical contexts, which influence how these texts are understood and accepted by readers. This study aims to analyze the role of texts and context in philosophical interpretation, as well as how their interaction gives rise to the diversity of existing schools of thought. Using a descriptive qualitative approach, this research analyzes philosophical texts from various intellectual traditions, both Western and Eastern, through an in-depth literature review. The findings of the study show that although philosophical texts contain profound and universal meanings, they can be interpreted in different ways depending on the social, political, and cultural context of the reader, resulting in various philosophical schools such as rationalism, empiricism, existentialism, and others. Academically, this research contributes to enriching the study of philosophy, particularly in understanding the dynamics of diverse text interpretations, as well as their relevance in religious and social studies. The study also emphasizes the importance of understanding context in reading philosophical texts to obtain a more contextual and inclusive understanding of the development of philosophical thought.